Going Beyond General Media Trust: An Analysis of Topical Media Trust, its Antecedents and Effects on Issue (Mis)perceptions. (19th August 2022) - Tsfati, Yariv; Strömbäck, Jesper; Lindgren, Elina; Damstra, Alyt; Boomgaarden, Hajo G; Vliegenthart, Rens
Abstract: A key problem with research on news media trust is that it has mostly focused on general media trust and that there is limited research on how media trust might vary across levels of analysis. In this paper, we seek to remedy this by investigating whether news media trust differs depending on the topic of news coverage and whether topical trust can be distinguished from general media trust. We also investigate the antecedents of trust in news coverage of different topics and the effects of topical trust on issue (mis)perceptions. Among other things, findings show that topical media trust can be distinguished from general media trust and is a better predictor of correct perceptions on political matters.